THE IMPACT OF COMPANY SIZE, SALES GROWTH, AND A NON-DEBT TAX SHIELD ON MANUFACTURING COMPANIES' CAPITAL STRUCTURE ON THE INDONESIA STOCK EXCHANGE - Novien Rialdy; Muhammad Fahmi (Universitas Putera Batam, 2023)
This study aims to determine whether 43 food and beverage companies listed on the Indonesia Stock Exchange's Capital Structure (DER) is affected by Company Size, Sales Growth, and Non Debt Tax Shield simultaneously or partially. Seven food and beverage companies that meet the criteria for sampling for this study are included in the study's samples.Company Size, Sales Growth, and Non Debt Tax Shield are the independent variables in this study, while Capital Structure (DER) is the dependent variable.This study uses secondary data, or information that is already available in the form of financial statements that are listed on the Indonesia Stock Exchange, as the method of data collection.With a significance level of 5%, the Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Testing, and Coefficient of Determination are utilized in this study's data analysis method. This study demonstrates that Sales Growth partially influences Capital Structure (DER), Company Size partially influences Capital Structure (DER), and Non Debt Tax Shield partially influences Capital Structure (DER).What's more, at the same time expressed that Organization Size, Deals Development and Non Obligation Assessment Safeguard influence the Capital Construction of Assembling Organizations on the Indonesia Stock Trade.